Rethinking how health care professionals cope with stress: A process model for COVID-19 and beyond. Issue 4 (5th October 2022) - Harley, Jason M.; Montreuil, Tina C.; Lou, Nigel Mantou; Feldman, Liane S.; Fried, Gerald M.; Lavoie-Tremblay, Mélanie; Bhanji, Farhan; Kennedy, Heather
Abstract : Issue: Prior to the COVID-19 pandemic, there was evidence of challenges surrounding the psychological well-being of health care professionals (HCPs). HCPs already frayed psychological ability to cope risks being further compromised by COVID-19-related stresses. Critical Theoretical Analysis: Most research on stress, psychological distress, and coping among HCPs is done in a piecemeal manner without a theoretical model connecting these different but related phenomena. This critical advancement article aims to apply and extend Wheaton and Montazer's model of stressors, stress, and distress to the literature on HCPs, generally, and COVID-19, specifically, to summarize past and guide future research on HCPs' mental health, resilience, and coping. Our model describes how different sources of support buffer the effect of stressors on stress and how coping strategies moderate the effect of stress on psychological distress. Advance: We extended the model by (a) distinguishing context from the support in HCPs' environment; (b) distinguishing adaptive from maladaptive coping strategies and their relationships with antecedents and outcomes; (c) describing the adverse impacts that psychological distress has on patients, HCPs, and health services; and (d) describing how such outcomes can become stressors, in turn, further contributing to HCPs' stress in a vicious cycle. Practice Implications: Our model provides a broader perspective of HCPs' work-related mental health and helps guide the creation, implementation, and evaluation of different sources of support and promote adaptive coping strategies. This model helps HCPs, researchers, and health services managers better understand and respond to the well-being crisis HCPs are facing, especially during the pandemic.